Magnetorheological brushes – scarcely explored class of magnetic material - Bastola, Anil Kumar (2023)
Magnetic materials such as magnetorheological (MR) fluids, and magnetorheological elastomers exhibit a broad change in their material properties, for example, viscosity and storage modulus in the presence of a magnetic field. Studies related to such MR fluid and elastomer materials are extensively available. The MR brush, meanwhile, is less frequently explored and understood. An MR brush is defined by the brush-like structures formed from chains of magnetic particles embedded within a carrier matrix, typically fluids or elastomers. In this study, we explore magnetorheological fluid (MRF) brush and magnetorheological elastomer (MRE) brush and investigate their magneto-mechanical properties. The investigation measured the stiffness and the MR response, defined as the change in properties in the presence of a magnetic field for MRF and MRE brushes. Further dependence of the magnetic effect on material and preparation parameters, mainly concentration of magnetic particles and curing flux density (for MRE brush) were investigated. The responsiveness of the brushes is compared using the Magnetorheological response index, as a proposed metric in this study. The results indicate that the MRE brush possess a greater absolute stiffness, but a lower MR response than that of the MRF brush. Both MRF and MRE brushes show an increase in the MR response with an increased concentration of magnetic fillers. MRE brush further demonstrate an enhanced MR response, which could be highly comparable to MRF brush coinciding with an increase in the magnetic flux density during the curing process. The fundamental investigation of both solid and fluid MR brushes in this study opens a new avenue in the area of magnetic materials. This new class of magnetically controllable materials could potentially be employed in applications where soft and tuneable bristle-like structures are desired.